Association of Medication Adherence and VKORC1 Polymorphisms with Stable Warfarin Dose Requirements in Patients with Mechanical Heart Valves - Syilvi Rinda Sari; Fendy Prasetyawan; Restu Anisa Putri (CV. Get Press Indonesia, 2025)
Warfarin remains the primary oral anticoagulant for patients with mechanical heart valves, but considerable interindividual variability in stable dose requirements poses a clinical challenge. Although VKORC1 gene polymorphisms are well-established determinants of dose variability, the impact of objectively measured medication adherence is less clear. This study aimed to evaluate the independent and combined effects of VKORC1 polymorphisms and objectively measured medication adherence on stable warfarin dose requirements in patients with mechanical heart valves. Genotyping of VKORC1 −1639G>A (rs9923231) and 1173C>T (rs9934438) was performed using PCR–RFLP. Adherence over 90 days was expressed as the percentage of prescribed doses taken. The −1639A allele frequency was 81.7%, and patients with the AA genotype required significantly lower daily doses than GA or GG genotypes (p<0.001). Mean adherence was 89.4±11.2%. Multivariate regression showed that VKORC1 genotype, age, and adherence independently predicted stable dose,explaining 45.2% of variability. Stable warfarin dose was defined as an unchanged maintenance dose with a therapeutic INR (2.0–3.5) for ≥3 months.Adherence below 80% was associated with increased INR fluctuations and dose adjustments, highlighting adherence as a key clinical modifier alongside genetic factors.